Preparing Blue Crab: A Seafood Delicacy - Donald E. Sweat (EDIS, 2007)
SGEF-120, a four-fold color brochure by Donald E. Sweat, illustrates how to pick the meat, and provides information on how to buy blue crabs. Published by the UF Sea Grant Extension Program, revised May 2007.